Effects of solutes on thermal stability, microstructure and mechanical properties in CrMnFeCoNi based alloys after high pressure torsion. (1st April 2022) - Keil, Tom; Taheriniya, Shabnam; Bruder, Enrico; Wilde, Gerhard; Durst, Karsten
Abstract: The equiatomic Cantor alloy and Ni-enriched derivates of it ((CrMnFeCo)x Ni1-x with x = 0.8, 0.4, 0.08 and 0) were deformed by high pressure torsion to the saturation regime and subsequently annealed in a wide temperature range. The microstructural stability of the alloys was investigated in terms of grain growth and decomposition tendencies with an emphasis on Ni92 and Ni60 that are marking a transition from dilute solid solutions to HEA alloys. Ni92 and Ni100 show a larger grain size after HPT than the HEA type alloys Ni20 and Ni60, yet, they do exhibit a lower resistance to grain growth. Both HEA type alloys exhibit decomposition tendencies in the form of secondary phases (Ni20) or nanosized Cr-rich precipitates and Mn segregations to grain boundaries (Ni60), that reduce the grain boundary mobility. A comparison of the activation energies for grain growth and diffusion coefficients of the alloys shows a good qualitative agreement. The differences in microstructural stability are also reflected by the mechanical properties. All alloys show a small amount of hardening after annealing, followed by a softening for higher temperatures in case of dilute solid solutions. In contrast, the hardness of the HEA type alloys remains constant up to 450 °C (Ni60) or even increases up to 500 °C (Ni20) followed by a softening at higher annealing temperatures. The second phase formation with limited volume fractions has no effect on the modulus. Graphical abstract: Image, graphical abstract .